Sallust’s account of corruption and its Western accomplices (2017)
The axiom, ‘it takes two to tango’ may fittingly describe how corruption thrives. While demonstrably endemic in and seemingly generic to Africa, the ancient history of corruption depicts active participation of Western accomplices; collaborators, who perpetrated and advanced their political interests with the proceeds of sleaze. This article, using the Roman historian Sallust’s Bellum Iugurthinum (The War with Jugurtha), employs interpretive approach to highlight how an African monarch was spurred on by corrupt leading Roman senator, who treated public assets as personal property, to recklessly pursue his political ambition. The article highlighted how Roman soldiers introduced the use of money in seeking power to Jugurtha and the stages of the former’s duplicity in the prolonged African conflicts. With evidence to support Jugurtha’s description of Rome in her corrupt state as ‘urbem venalem et mature perituram, si emptorem invenerit’ (a city for sale and doomed to speedy destruction if it finds a purchaser- Sallust, Jugurthine War 35.10), the conclusion is: the African ruler got in the Roman senate a viral school of bribery. Interestingly, the episode of corruption ended when the will of the corrupt Roman senators was thwarted. Therefore, mitigating corruption could begin from the West that hosts its influential accomplices.